Digital Transformation of Islamic Vocational Education in the Industry 5.0 Era: A Prisma-Based Review - Ahmad Sholahuddin (Generate Digital Publishing, 2026)
Objective: This study systematically maps the forms, strategies, achievements, and challenges of digital transformation in Islamic vocational education in response to the Industry 5.0 era, emphasizing the integration of digital competencies, Islamic values, and industry relevance. Research Design & Methods: A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 guidelines. Literature was collected from Scopus, Web of Science, Google Scholar, DOAJ, and SINTA databases covering publications from 2019–2025. From 612 initial records, 34 eligible articles were selected and analyzed using thematic analysis. Findings: Five major themes emerged: (1) digitization of curricula and learning materials grounded in Islamic values; (2) enhancement of digital literacy among students and educators; (3) integration of adaptive learning technologies and artificial intelligence; (4) institutional, infrastructural, and digital divide challenges; and (5) the transformation of vocational education toward a human-centric Industry 5.0 model. The review reveals that successful digital transformation depends on visionary leadership, human resource readiness, adequate technological infrastructure, and the effective integration of spiritual values into digital learning environments. Contributions: This study provides a comprehensive synthesis of digital transformation trends in Islamic vocational education and offers practical insights for policymakers, educational leaders, and industry stakeholders in developing vocational education models aligned with Industry 5.0 requirements. Novelty: This study proposes an integrative model connecting technological competence, Islamic character, and industry relevance to enhance workforce readiness in the Industry 5.0 era while synthesizing fragmented literature on digital transformation in Islamic vocational education.